Characterization of two novel chia (Salvia hispanica L.) white and black genotypes via DNA barcoding, physiological, and agronomic traits - Clara R. Azzam; Mokhtar Said Rizk; Soha Sayed Mohammad Mostafa; Ramadan A. Arafa; Mohamed Samy Al-Nabawi; Nahid Abdelaty Ali Morsi; Marwa Mahmoud Nasr El-Din; Enass Hassan Taher; Khaled Adly Khaled (Journal of Genetic Engineering and Biotechnology)
Background: Chia (Salvia hispanica L.) is recognized for its nutritional value and health-promoting compounds, including flavonoids. Aim: This study utilized DNA barcoding to identify and differentiate two novel chia genotypes, CACH-W and CACH-B, providing insights for breeding programs and genetic resource conservation (CA refers to the developer and CH refer to Chia). Methods: DNA was extracted from controlled samples and analyzed using five barcode markers: trnH-psbA, matK, rpoC1, rbcL, and ITS. Genetic diversity was evaluated through phylogenetic analysis with appropriate bioinformatics tools. Results: DNA barcoding using five markers (trnH-psbA, matK, rpoC1, rbcL, and ITS) successfully amplified sequences of 930 bp, 1520 bp, 2295 bp, 1910 bp, and 1630 bp, respectively. Among them, rbcL, rpoC1, and ITS effectively differentiated the two genotypes, and phylogenetic analysis confirmed their genetic identity and relationship with existing (Salvia hispanica L.) sequences. Functional analyses highlighted the conserved roles of key genes, including rbcL (carbon fixation), rpoC1 (chloroplast transcription), and matK (RNA splicing). The white genotype (CACH-W) outperformed the black genotype (CACH-B) in germination, physiological, and agronomic traits, achieving a higher seedling vigor index (11.68 vs. 8.51), longer radicle (6.94 cm vs. 5.02 cm), and greater total phenolic content (31.92 mg/g vs. 28.95 mg/g). Agronomically, CACH-W showed superior plant height, spike weight, and seed yield (1003.83 kg/feddan vs. 606.46 kg/feddan), making it a promising candidate for cultivation and breeding. Conclusion: This study demonstrates the effectiveness of certain plastome gene sequences in identifying and distinguishing chia varieties, offering a reliable tool for breeding, quality control, and germplasm conservation. The white genotype (CACH-W) outperformed the black genotype (CACH-B) in germination, physiological, and agronomic traits, achieving a higher seedling vigor index, longer radicle, and greater total phenolic content. Agronomically, CACH-W showed superior plant height, spike weight, and seed yield, making it a promising candidate for cultivation and breeding. The results also support the integration of marker-assisted selection for developing chia varieties with improved traits, enhancing their commercial and agricultural value.